2014
DOI: 10.1039/c3cp55352c
|View full text |Cite
|
Sign up to set email alerts
|

Chirped-pulse millimeter-wave spectroscopy for dynamics and kinetics studies of pyrolysis reactions

Abstract: A Chirped-Pulse millimeter-Wave (CPmmW) spectrometer is applied to the study of chemical reaction products that result from pyrolysis in a Chen nozzle heated to 1000-1800 K. Millimeter-wave rotational spectroscopy unambiguously determines, for each polar reaction product, the species, the conformers, relative concentrations, conversion percentage from precursor to each product, and, in some cases, vibrational state population distributions. A chirped-pulse spectrometer can, within the frequency range of a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 91 publications
0
57
1
2
Order By: Relevance
“…The SO 2 (Sigma Aldrich, 99.9%) was seeded at 0.5% in the helium flow and dissociated using an ArF excimer laser. To monitor the appearance of the product, the "fast-frame" capability of the oscilloscope was used, 7,11 such that successive spectra were obtained at 5 μs intervals following an initial 10 μs delay between the laser trigger and the first chirped pulse excitation. Ten frames (i.e., spectra) obtained in this fashion, each an average of roughly 6500 acquisitions, are shown in Fig.…”
Section: B Photochemistry: So 2 + Hν (193 Nm) → O ( 3 P J ) + So (X mentioning
confidence: 99%
See 2 more Smart Citations
“…The SO 2 (Sigma Aldrich, 99.9%) was seeded at 0.5% in the helium flow and dissociated using an ArF excimer laser. To monitor the appearance of the product, the "fast-frame" capability of the oscilloscope was used, 7,11 such that successive spectra were obtained at 5 μs intervals following an initial 10 μs delay between the laser trigger and the first chirped pulse excitation. Ten frames (i.e., spectra) obtained in this fashion, each an average of roughly 6500 acquisitions, are shown in Fig.…”
Section: B Photochemistry: So 2 + Hν (193 Nm) → O ( 3 P J ) + So (X mentioning
confidence: 99%
“…Moreover, the broadband detection scheme readily allows for comparison of relative line intensities of different species to provide accurate branching ratios if the products have a well-defined rotational temperature. 11 In a recent CP study, a signature of roaming dynamics was observed by quantifying branching into several reaction products aided by accurate kinetic modeling. 14 As a form of rotational spectroscopy, CP-FTMW requires cold samples to produce sufficiently large population differences for sensitive spectroscopic detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the intensities of the spectral lines are reliable indicators of relative species' populations, making it possible to accurately determine branching ratios and, in some cases, vibrational distributions. 31 Thus, when combined with a PUSF source, this combined CPUF technique is uniquely well-suited for studying polyatomic unimolecular and bimolecular reaction dynamics and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Fine structure in the chirpedpulse spectrum of the prism isomer of the water hexamer enables the measurement of hydrogen-bond network rearrangement [3]. Prozument et al [4] have used chirped-pulse millimeter wave spectroscopy to obtain meaningful product branching ratios and vibrational population distributions from a flash pyrolysis reactor. Recent work in the A. G. Suits lab [5,6] has demonstrated the use of time-domain CP-FTMW measurements to measure the vibrationally-specific rate of appearance of unimolecular and bimolecular reaction products in a cold uniform flow.…”
mentioning
confidence: 99%